Sulfur and molybdenum fractionation in marine and riverine alluvium paddy soils - Zakikhani, Hamed; Yusop, Mohd Khanif; Musa, Mohamed Hanafi; Othman, Radziah; Soltangheisi, Amin (Taylor & Francis, 2016)
Intermittently submergence and drainage status of paddy fields can cause alterations in morphological and chemical characteristics of soils. We conducted a sequential fractionation study to provide an insight into solubility of Sulfur (S) and Molybdenum (Mo) in flooded alluvial paddy soils. The samples (0-15 and 15-30 cm) were taken from marine and riverine alluvial soils in Kedah and Kelantan areas, respectively, and were sequentially extracted with NaHCO3, NaOH, HCl, and HClO4-HNO3. Total S in upper and lower layers of Kedah and Kelantan ranged between 273 and 1121 mg kg-1, and 177 to 1509 mg kg-1, respectively. In upper layers and subsoil of Kedah, average total Mo were 0.34 and 0.27 mg kg-1, respectively. Average total Mo in Kelantan were 0.25 mg kg-1 (surface layer) and 0.28 mg kg-1 (subsoil). Cation exchange capacity (CEC) was positively correlated with plant available amounts of Mo in upper layers of Kedah area. Also, total and medium-term plant-available S was correlated with total carbon (C) at lower layers of Kelantan soil series. But in surface layers of Kelantan soil series, CEC was strongly correlated with total and medium-term plant-available S. Our results indicates that the influence of flooding conditions on soil S and Mo contents in paddy fields may cause long-term changes in S and Mo chemical reactivities.